Characterization of caesarean deliveries in primiparous women: a cross-sectional study - Cardoso Matos, Khesia Kelly; Correia Pacheco, Álvaro José; Soares dos Santos, Sara; de Araújo Nascimento, Emanuela; Oliveira Neves, Linda Kelly; de Oliveira Nunes, Gittanha Fadja; de Souza Lima, Juciara Karla (O Mundo da Saúde, 2018)
The objective of the study was to describe as characteristics of caesarean births of primiparous women in a hospital in the São Francisco Valley in the year 2013. Descriptive, retrospective and cross-sectional study with 101 pregnant women undergoing caesarean section. The data were collected from the patients’ medical records using a form and analyzed through the EPI INFO 3.7 program. It was observed that the mean age of the primiparous women was 21 years, 96.3% were brown, 69.3% had a partner, and 49.4% had 12 or more years of education. Pre-eclampsia (15.84%) and progression dystocia (14.85%) were the main referrals for caesarean section. Of those surveyed, 80% had no previous risk factor. However, 27.6% had hypertensive complications, 7.9% had hemorrhagic complications, and 9.9% already needed ICU admission. Characteristics of the studied population were young women with a partner, good schooling, brown and prenatal. The main referrals for a caesarean section were: pre-eclampsia and progression dystocia, although they did not have any previous risk factor, they presented hemorrhage and hypertensive disease as a complication, and were admitted to the ICU was the most frequently found maternal morbidity condition.